Optimization of Sorghum Starch (Sorghum bicolor L.) Partial Hydrolysis using Microwave-Assisted Acetic Acid Catalyst - Sitio, Septi Enjelina; Nurlaili, Fitri Dwi; Riadhus Shalihin, Muhammad Zaki; Amalia, Rizka; Paramita, Vita (agriTECH, 2024)
Hydrolysis process is relatively slow, requiring the use of catalyst and microwave assistance to accelerate the reaction. There fore, this study aimed to determine the optimum conditions for partial hydrolysis of sorghum starch (Sorghum bicolor L.) using acetic acid as a microwave-assisted catalyst to produce maltodextrin. The experiment was carried out in several stages, namely gelatinization, liquefaction, and drying, while Response Surface Method (RSM) was used for variable design and data analysis. Hydrolysis process was carried out with three independent variables, including acetic acid concentration (9%, 12%, and 15%), microwave power (300 watts, 400 watts, and 500 watts), and liquefaction time (35 minutes, 45 minutes, and 55 minutes). The results showed that the highest DE (Dextrose Equivalent) value of maltodextrin was found at 17.04% acid concentration, 400 watts microwave power, and 45 minutes liquefaction time, valued at 18.921 ± 0.099. The optimum dextrose equivalent of 17.763 would be achieved at 16.879% acetic acid concentration, 390.233 watts of microwave power, and 47.055 minutes of liquefaction time. This study introduces the innovation of using acetic acid as a catalyst and microwave assistance during the gelatinization stage.